A new coefficient of economic valuation based on utility scores - Mariani, Paolo; Mussini, Mauro (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
This paper proposes a new coefficient for measuring economic valuation based on utility scores and attribute importance values derived from standard conjoint analysis. The coefficient allows to quantify the impact of a change in an attribute of a good or service in monetary terms. We utilize the suggested coefficient for the economic valuation of a worldwide cultural event to reveal the trade-offs among its attributes in terms of total revenue variation. In addition, our findings indicate how the user degree of satisfaction affects the determinants of demand in generating an economic surplus or shortfall
Argumenta Oeconomica, 2013, Nr 1 (30), s. 33-46
Keywords: conjoint analysis; willingness-to-pay; economic valuation; valuation of public goods; pomiar wieloczynnikowy; wartość ekonomiczna; dobra publiczne